2020
DOI: 10.1093/dote/doaa021
|View full text |Cite
|
Sign up to set email alerts
|

Totally minimally invasive esophagectomy versus hybrid minimally invasive esophagectomy: systematic review and meta-analysis

Abstract: Summary Minimally invasive esophagectomy is increasingly performed for the treatment of esophageal cancer, but it is unclear whether hybrid minimally invasive esophagectomy (HMIE) or totally minimally invasive esophagectomy (TMIE) should be preferred. The objective of this study was to perform a meta-analysis of studies comparing HMIE with TMIE. A systematic literature search was performed in MEDLINE, Embase, and the Cochrane Library. Articles comparing HMIE and TMIE were included. The Newcastle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 46 publications
1
21
1
Order By: Relevance
“…There is also increasing interest in the usage of robotic assisted platforms for oesophagectomy [19]. Both hybrid and totally MIA oesophagectomy show improved peri-operative outcomes and at least equivalent survival outcomes when compared with open procedures [13,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…There is also increasing interest in the usage of robotic assisted platforms for oesophagectomy [19]. Both hybrid and totally MIA oesophagectomy show improved peri-operative outcomes and at least equivalent survival outcomes when compared with open procedures [13,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, a higher anastomotic leakage rate was reported for TMIE than hybrid oesophagectomy. The meta-analysis 27 that compared TMIE with hybrid oesophagectomy reported a significant increase in anastomotic leakage rate for TMIE compared with hybrid Ivor Lewis oesophagectomy. This was most probably due to the technically challenging minimally invasive intrathoracic anastomosis.…”
Section: Eccg Databasementioning
confidence: 98%
“…[9][10][11][12][13][14] However, because a totally minimally invasive transthoracic esophagectomy is a challenging and demanding procedure, some esophageal surgeons still perform open (OE) or hybrid esophagectomy (HE). [15][16][17][18][19][20] The aim of this systematic review and meta-analysis was to compare surgical outcomes between OE, HE, and totally minimally invasive Ivor Lewis esophagectomy (TMIE).…”
Section: Perspectivementioning
confidence: 99%